The problem of self-refutation: is consistent relativism possible? - Terekhin, Evgeny L. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article explores the possibility of a consistent and philosophically promising relativism, primarily in the context of considering the main argument of its opponents and critics – accusations of self-refutation. The concept of radical relativism is interpreted as inconsistent with the basic foundations of classical epistemology. In the course of the study, a historical and philosophical reconstruction of the tradition of using the argument of self-refutation of relativism was carried out. Three possible options for relativism to avoid accusations of self-refutation are identified: to remain at the level of local relativism, to claim the status of a metatheory, to affirm the truth of relativism as relative. It is shown that epistemological relativism, being one of the forms of the so-called local relativism, still cannot a priori avoid accusations of self-refutation, and relativism’s claims to the status of a metatheory cannot be adequately substantiated. The adoption of the program of substantiation of the relative truth of the relativistic paradigm opens up a real prospect of overcoming the argument of the self-refutation of relativism, at least in the form that has been established in classical epistemology since Plato.